Muqāranah Afkār al-Tawḥīd ‘inda al-Syaikh ‘Abd al-Jabbār wa Abī al-Ḥasan al-‘Asy’arī - Ma'afi, Rif'at Husnul; Al Faruqi, Achmad Reza Hutama; Taufiqurrahman, Azhar; Chaidir, Ahmad (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
This article discusses Tauhid by two prominent mutakallim figures, namely al-Qāḍī ‘Abd al-Jabbār and al-‘Ash’arī using literature review and analytical and comparative methods. These two figures have similarities and differences in the concept of tauhid. ‘Abd al-Jabbār denies the azaliyah qualities that Allah has attached to Himself, because pinning these qualities to Allah will have an impact on divine dualism, and will also plunge a person into tajsim and tasybih, so he sees that Allah's nature is in essence, God himself. This statement was then opposed by al-Ash’arī, arguing that the nature of Allah is not His essence and nothing else, it means that the attributes of Allah are qadim. This is what the Mu’tazilah denied because it causes the number of qadim to be counted. The results of this study conclude that they agree on the oneness of Allah and provide evidence for it, refute things that lead to tasybih and tajsim, and takyif against Allah SWT. In addition, denying the possibility of seeing Allah in the world, and believing that Allah has the nature of kalam even though they differ in defining these attributes. While the difference between these two figures, first is in terms of their manhaj in determining aqidah. Second, in interpreting monotheism, the relationship between essence and nature, the nature of faith, interpretation of mutasyabih verses, the word of God, ru’yatullah in the hereafter.